2009
DOI: 10.1536/ihj.50.731
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Diagnosis of Cardiac Sarcoidosis Using Microvolt T-Wave Alternans

Abstract: SummarySarcoidosis is a systemic granulomatous disorder whose prognosis worsens when the heart is involved, and early diagnosis is important. Endomyocardial biopsy is the most helpful diagnostic examination, but suffers from low sensitivity and low specificity. Microvolt T wave alternans (MVTWA) is utilized in noninvasive examinations to detect beat-tobeat changes in the shape of the T wave at the microvolt level. Such beat-to-beat T wave changes arise from beat-to-beat changes in the transmural gradient of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This test in a recent small 35-patient study revealed ability to detect cardiac sarcoidosis with 85.7% sensitivity and 92.8% specificity. 19 Echocardiography, Holter monitoring, SAECG, and MVTWA are all relatively inexpensive and readily available tools that can help to risk-stratify patients early for the need for further diagnostic evaluation. gold standard for diagnosis of cardiac involvement in sarcoidosis.…”
Section: Clinical Manifestations and Electrocardiogram Findingsmentioning
confidence: 99%
“…This test in a recent small 35-patient study revealed ability to detect cardiac sarcoidosis with 85.7% sensitivity and 92.8% specificity. 19 Echocardiography, Holter monitoring, SAECG, and MVTWA are all relatively inexpensive and readily available tools that can help to risk-stratify patients early for the need for further diagnostic evaluation. gold standard for diagnosis of cardiac involvement in sarcoidosis.…”
Section: Clinical Manifestations and Electrocardiogram Findingsmentioning
confidence: 99%
“…There have been few reports on TWA in sarcoidosis. Although one study reported the utility of TWA for detecting cardiac involvement in patients with sarcoidosis, their sample size was similarly small 25 . A large‐scale study is required to evaluate the utility of TWA in patients with sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other repolarization abnormalities reported in some studies include increased QT dispersion ( 135 ), the presence of microvolt T-wave alternans ( 136 ), higher T-wave amplitude in lead aVR ( 137 ), T-wave inversion ( 128 ), and a longer interval of T-peak to T-end ( 126 ).…”
Section: Ecg In Acquired Forms Of Cardiomyopathy: Sarcoidosismentioning
confidence: 99%